Pendidikan Demokrasi Sebagai Alat Penguat Kebhinekaan Dan Toleransi Di Sekolah - Fadhila Az Zahra; Dea Nabila (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Democratic education is an important element in forming a just and inclusive society, especially in a country with high diversity like Indonesia. This research aims to explore the role of democratic education in strengthening diversity and tolerance in schools. The research method used is a qualitative approach with a focus on case studies in several junior high schools in Indonesia. The research results show that although democracy education has been integrated into the curriculum through Citizenship Education (PKN) subjects, its implementation is often still theoretical and does not facilitate active student participation. The main challenges in implementing democratic education include limited resources, lack of training for teachers, and school environments that are not yet fully inclusive. However, there are several positive initiatives that have succeeded in integrating democratic education in an innovative way, such as election-like class president elections, debate programs, and community service projects. Effective democratic education can increase tolerance, leadership skills, critical thinking abilities, and students' awareness of the importance of participation in democratic life. To increase the effectiveness of democratic education, more intensive training for teachers, a more practical and participatory curriculum, and an inclusive school environment are needed. In this way, it is hoped that democratic education can form a young generation that is more inclusive, tolerant and ready to actively participate in democratic life in Indonesia.